PENGARUH KARAKTER EKSEKUTIF, KOMISARIS INDEPENDEN DAN KOMITE AUDIT TERHADAP PENGHINDARAN PAJAK DENGAN KETIDAKPASTIAN LINGKUNGAN SEBAGAI MODERASI - Annisa Sakra Rinjani (2022)
The purpose of this study was to determine the effect of the character executive, independent commissioner and audit committee on tax avoidance by adding environmental uncertainty as moderating variable. This is a quantitative study using secondary data from manufacturing companies listed on Indonesia Stock Exchange for the 2017-2020 period. Purposive sampling method was used to select samples with a final result of 333 samples. The analytical technique used is Multiple Linear Regression Analysis with Moderated Regression Analysis (MRA) method using STATA version 16 program and a significance level of 5%. From the results of the tests carried out, it can be concluded that (1) the executive character has a significantly negative effect on tax avoidance, (2) independent commissioners have no effect on tax avoidance, (3) the audit committee has a significantly negative effect on tax avoidance, (4) uncertainty environment does not moderate the effect of executive character on tax avoidance, (5) environmental uncertainty does not moderate the effect of independent commissioners on tax avoidance, (6) environmental uncertainty does not moderate the effect of audit committee on tax avoidance.